2018
DOI: 10.1128/jvi.01824-17
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Functional Characterization of GII.4 Norovirus-Encoded NTPase

Abstract: The genotype II.4 (GII.4) variants of human noroviruses (HuNVs) are recognized as the major agent of global gastroenteritis outbreaks. Due to the lack of an efficient cell culture system for HuNV propagation, the exact roles of HuNV-encoded nonstructural proteins (including Nterm, NTPase, P22, VPg, Pro, and RdRp) in viral replication or pathogenesis have not yet been fully understood. Here, we report the molecular characterization of the GII.4 HuNV-encoded NTPase (designated GII-NTPase). Results from our studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 42 publications
(60 reference statements)
5
36
0
Order By: Relevance
“…All were reported to form homooligomeric ring-like structures in vitro, combined with high activity. More recently, a cellular localization study for GII.4 norovirus NTPase demonstrated that this protein can form homodimers and homooligomers through a head-to-head, head-to-tail, or tail-to-tail configuration [41]. These reports support our finding that MNV NS3 forms homooligomers.…”
Section: Discussionsupporting
confidence: 89%
“…All were reported to form homooligomeric ring-like structures in vitro, combined with high activity. More recently, a cellular localization study for GII.4 norovirus NTPase demonstrated that this protein can form homodimers and homooligomers through a head-to-head, head-to-tail, or tail-to-tail configuration [41]. These reports support our finding that MNV NS3 forms homooligomers.…”
Section: Discussionsupporting
confidence: 89%
“…4). NS3 has been characterized as a nucleoside triphosphatase (NTPase), and we and others have recently shown that it is associated with the viral replication complex, the ER, mitochondria, lipids, and microtubules (36)(37)(38). NTPases have diverse activities and functions, including an association with microtubule dynamics, intracellular transport, and protein degradation (39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NV NTPase possesses fundamental enzymatic activities that play a significant role in viral replication, such as (a) NTP-dependent helicase activity for unrolling of RNA helices, (b) NTP-independent chaperone activity for remodeling of the RNA structure and facilitating the annealing of the RNA chains, and (c) collaboration in RNA synthesis carried out by NS7 (62). Significantly, the subcellular localization of the GII.4 NTPase protein was determined through a confocal immunofluorescence analysis in human melanoma A7 cells, determining that this protein can form vesicular and nonvesicular structures in the cell cytoplasm (63). Besides that, the non-vesicular form of NTPase can be located in the ER or the membrane of the cellular mitochondria.…”
Section: Ntpasementioning
confidence: 99%
“…Besides that, the non-vesicular form of NTPase can be located in the ER or the membrane of the cellular mitochondria. The amino acid 179 of the N-terminal region is necessary for the formation and the localization of vesicles in the ER (63). On the other hand, for mitochondrial localization, the NTPase C-terminal region of GII plays a significant role, even when the N-terminal NTPase region is completely removed (63).…”
Section: Ntpasementioning
confidence: 99%
See 1 more Smart Citation